PERANCANGAN PROSES BISNIS APLIKASI PADA ARSITEKTUR SISTEM PEMERINTAHAN BERBASIS ELEKTRONIK (SPBE) KOTA DENPASAR - Wijaya, I Nyoman Yudi Anggara; Adiyana, I Made Alit; Juliharta, I Gede Putu Krisna (Institut Bakti Nusantara, 2024)
One of Bali's development missions is to develop a local governance system that is effective, efficient, open, transparent, accountable and clean and to improve integrated, fast and cheaper public services. As a form of transformation from the E-Government era, in 2018 the Government of Indonesia issued Presidential Regulation (Perpres) No. 95 of 2018, concerning the Electronic-Based Government System (SPBE) which includes central government, regional government and city government which aims to create efficient, effective and transparent governance as well as create quality and reliable public services. Denpasar City is one of the cities whose government has implemented various information systems as a form of Electronic Based Government (SPBE) implementation which refers to Perwali Denpasar No. 28 of 2021. In 2021, the Denpasar City Government will evaluate the implementation of the SPBE that has been running so far. The index value of the evaluation is 3.19 and is classified as good. From the results of the evaluation that has been carried out, it was found that in the SPBE Management Implementation domain the lowest score was obtained compared to other aspects. Based on these conditions, it is necessary to make efforts to improve the design of information systems from various aspects such as organizational business process architecture, data, applications, and technology in order to form integrated SPBE services.